EFFECT OF CHESTNUT HYDROLYSABLE TANNIN ON WEIGHT MANAGEMENT AND OVARIAN HISTOPATHOLOGY OF HEALTHY FEMALE RATS - F.Manzoor; M. N. Nisa; H. A. Hussain; N. Ahmad1and H. Umbreen (Journal of Animal and Plant Sciences, 2020)
The hydrolysable Tannin (HT) is one of the phenolic compounds extracted from different vegetables and plants. The study was planned to evaluate the effect of HT on the weekly body weight gain, nutrient intake and ovarian histopathology of the healthy female rats. The 45 female rats (135g±5g) were completely randomized into five groups i.e. HT0.5, HT1, HT1.5 & HT2 while HT0 was considered control group. The rats were offered different levels of HT 0.5,1, 1.5 and 2% in solution form through oral gavage method once in a day for six weeks. A significant decrease was observed (P≤0.05) in weekly body weight, nutrient intake and weight gain of healthy female rats. No effect on water intake was observed (P>0.05). The histopathology showed a well defined primary and secondary follicles, corpora lutea and graffian follicles. In conclusion the HT has shown negative effect on the nutrient intake but it has shown positive effect in reducing body weight of animals while no prominent histopathological changes and no signs of inflammation, follicular atresia or no detrimental effects were observed on the structural integrity of the ovaries of healthy female rats.
Keywords: Hydrolysable tannin; Body weight gain; Nutrient intake; Histopathology